Jeersannidhi Award Lecture - Biological Control -- A success story - SEN, BINEETA (Indian Phytopathology, 2002)
The biological control of major soilborne pathogens in agriculturally important crops with Aspergillus niger, a less exploited biocontrol agent, is discussed.